Pengaruh Literasi Digital terhadap Minat Baca Siswa Kelas V SD Al Munawaroh Sentani - Embun Pridyanti Trikora; Anis Dyah Fitriana; Alma Pratiwi Husain; Luluk Wahyu Nengsih; Wulida Arina Najwa (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2023)
The aim of this research is to determine the effect of digital literacy on reading interest in fifth grade students at Al Munawaroh Elementary School, Sentani Regency. This research is quantitative with a survey method. Based on the results of hypothesis testing using normality, linearity, correlation, coefficient of determination and linear regression tests, the results obtained were t(count )= 2.689, which means that digital literacy has an effect on students' reading interest. Apart from that, the r value shown is 0.453, which means there is a "medium" relationship between digital literacy and students' reading interest.